2016
DOI: 10.1007/s00787-016-0909-3
|View full text |Cite
|
Sign up to set email alerts
|

Do child healthcare professionals and parents recognize social-emotional and behavioral problems in 1-year-old infants?

Abstract: Growing evidence supports the existence of clinically significant social-emotional/behavioral (SEB) problems among as young as 1-year-old infants. However, a substantial proportion of early SEB problems remain unidentified during contacts with child healthcare professionals. In this study, child healthcare nurse (CHCN; N = 1008) and parental (N = 518) reports about SEB worries were gathered, along with the maternal and paternal Brief Infant-Toddler Social and Emotional Assessment (BITSEA) ratings, for 12-month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Because the current study was part of a larger research project focusing on infants'/toddlers' SEB development, data collection was carried out in the context of routine well-child visits, and it was voluntary-based for parents (Alakortes et al, 2015;Alakortes et al, 2016), the main emphasis of the data collection was given to child characteristics and functioning, and the amount and type of questions addressing parental characteristics were limited to minimal and neutral. Consequently, in this study, the main focus of parental factors was given to parenting stress, although other parental characteristics such as parental psychopathology and marital discord also have been found to be potential moderators of interparental discrepancies in behavior ratings of older offspring (Christensen et al, 1992, Jensen et al, 1988Treutler & Epkins, 2003).…”
Section: Rationale and Aims Of The Current Studymentioning
confidence: 99%
“…Because the current study was part of a larger research project focusing on infants'/toddlers' SEB development, data collection was carried out in the context of routine well-child visits, and it was voluntary-based for parents (Alakortes et al, 2015;Alakortes et al, 2016), the main emphasis of the data collection was given to child characteristics and functioning, and the amount and type of questions addressing parental characteristics were limited to minimal and neutral. Consequently, in this study, the main focus of parental factors was given to parenting stress, although other parental characteristics such as parental psychopathology and marital discord also have been found to be potential moderators of interparental discrepancies in behavior ratings of older offspring (Christensen et al, 1992, Jensen et al, 1988Treutler & Epkins, 2003).…”
Section: Rationale and Aims Of The Current Studymentioning
confidence: 99%
“…Previous UAE-based studies in this area date back to 1998 [33] and 2004 [34], and more up-to-date data are required. It is of particular concern that many social, emotional and behavioral problems among young children are not identified during pediatric healthcare contacts [35], which suggests a preventive approach is necessary. An initial national epidemiological study is needed to clarify the extent of the problem in the UAE, increase awareness of this issue, and inform further interventional studies.…”
Section: Introductionmentioning
confidence: 99%
“…Community screening of infants’ mental health may be provided as a part of the general child health surveillance, which in many European countries includes services delivered by health visitors [50]. Research based on these settings indicates potentials for mental health screening for socio-emotional and behavioral problems in 1-year-olds [51], and 2-year-olds [52], psychosocial problems in 2-year-olds [53], and neuro-developmental problems in 30 months children [54]. A general population-based Danish study embedded in the settings of community health nurses (CHNs) has identified several infancy markers of psychopathology in preschool ages [22, 28, 55].…”
Section: Introductionmentioning
confidence: 99%